Interventional Pulmonology: The Role of Simulation Training and Competency-Based Evaluation - Desai, Neeraj R.; Parikh, Mihir S.; Lee, Hans J. (Seminars in Respiratory and Critical Care Medicine, 2018)
Medical education and training are becoming more complex endeavors as technological and research advancements lead to new tools and methods to care for patients. In recent years, there has been a paradigm shift in medical education to competency-based assessments. Another important recent development in medical education has been the increasing use of simulation-based learning for procedural training. Interventional pulmonology (IP) is a relatively young and rapidly evolving procedural-based subspecialty. There are several well-validated competency-based assessment tools available to measure training adequacy in many of the most commonly performed procedures in IP. These tools have been shown to improve learning curves and training outcomes. The extent of how widely these tools are being used in clinical and educational spheres, however, remains unclear. Moreover, several commonly performed procedures in IP have no or limited validation tools currently available. Standardized training using simulation has also been shown to lead to positive training outcomes as compared with more traditional training models. However, widespread adoption of simulators has been limited due to the cost and availability.
Keywords: simulation; competency-based medical education; interventional pulmonology; bronchoscopy; endobronchial ultrasound